An Overview of the CNS-Pharmacodynamic Profiles of Nonselective and Selective GABA Agonists - Chen, Xia (Hindawi Publishing Corporation, 2012)
Various α (2,3) subtype selective partial GABA-A agonists are in development to treat anxiety disorders. These compounds are expected to be anxiolytic with fewer undesirable side effects, compared to nonselective GABA-A agonists like benzodiazepines. Several α (2,3) subtype selective and nonselective GABA-A agonists have been examined in healthy volunteers, using a battery addressing different brain domains. Data from five placebo-controlled double-blind studies were pooled. Lorazepam 2 mg was the comparator in three studies. Three α (2,3)-selective GABAA agonists (i.e., TPA023, TPACMP2, SL65.1498), one α (1)-selective GABAA agonists (zolpidem), and another full agonist (alprazolam) were examined. Pharmacological selectivity was assessed by determination of regression lines for the change from baseline of saccadic-peak-velocity- (ΔSPV-) relative effect, relative to changes in different pharmacodynamic endpoints (ΔPD). SPV was chosen for its sensitivity to the anxiolysis of benzodiazepines. Slopes of the ΔSPV-ΔPD relations were consistently lower with the α (2,3) selective GABA-A agonists than with lorazepam, indicating that their PD effects are less than their SPV-effects. The ΔSPV-ΔPD relations of lorazepam were comparable to alprazolam. Zolpidem showed relatively higher impairments in ΔPD relative to ΔSPV, but did not significantly differ from lorazepam. These PD results support the pharmacological selectivity of the α (2,3)-selective GABA-A agonists, implying an improved therapeutic window.